2021
DOI: 10.3390/plants10091864
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and Divergence: Signal Perception and Transduction Mechanisms of Cold Stress in Arabidopsis and Rice

Abstract: Cold stress, including freezing stress and chilling stress, is one of the major environmental factors that limit the growth and productivity of plants. As a temperate dicot model plant species, Arabidopsis develops a capability to freezing tolerance through cold acclimation. The past decades have witnessed a deep understanding of mechanisms underlying cold stress signal perception, transduction, and freezing tolerance in Arabidopsis. In contrast, a monocot cereal model plant species derived from tropical and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 140 publications
(149 reference statements)
0
18
0
Order By: Relevance
“…Kinases and their profile expressions under cold stress have been recently reported in Brassica napus [112], Jatropha curcas [113], and Common vetch [114]. The Mitogen-Activated Protein Kinase (MAPK) cascade regulates cold stress through the binding roles of Calcium/Calmodulin-Regulated Receptors Kinase-Like 1 (CRKL1) [115]. Research on the MAPK cascade in Arabidopsis has demonstrated that CRLK1/2 interacts with the MEKK1, a MAPK module responding to lower temperatures [116].…”
Section: Mitogen-activated Protein Kinase (Mapk) Cascade and Hormonal...mentioning
confidence: 99%
“…Kinases and their profile expressions under cold stress have been recently reported in Brassica napus [112], Jatropha curcas [113], and Common vetch [114]. The Mitogen-Activated Protein Kinase (MAPK) cascade regulates cold stress through the binding roles of Calcium/Calmodulin-Regulated Receptors Kinase-Like 1 (CRKL1) [115]. Research on the MAPK cascade in Arabidopsis has demonstrated that CRLK1/2 interacts with the MEKK1, a MAPK module responding to lower temperatures [116].…”
Section: Mitogen-activated Protein Kinase (Mapk) Cascade and Hormonal...mentioning
confidence: 99%
“…However, long-term S fumigation broke this balance, which was manifested by the decrease of SOD and POD activities and a significant increase of MDA. This physiological response of S fumigation is similar to the defense of plants under drought, salt, and cold stresses (Auler et al, 2021;Wei et al, 2021;Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…The degradation of AtSPIRAL1 results in the depolymerization of MTs, followed by the formation of new MTs that are better adapted to osmotic stress ( Wang et al, 2011 ). For another target gene AhSRF , recent evidence has shown that homologous gene AtSRF6 is an identified regulator for COR in Arabidopsis ( Wei et al, 2021 ). These reports suggest that the miR1511- SRF and miR1511- SPIRAL1 modules may attenuate cold tolerance by mediating MT stability or by regulating the ICE-CBF-COR pathway.…”
Section: Discussionmentioning
confidence: 99%